Відповідь: n/[ 2( 3n + 2 ) ] .
Пояснення:
Нехай А = 1/(2*5) + 1/( 5*8) + 1/( 8*11 ) +...+ 1/ [ (3n-1)*(3n+2) ] , тоді,
внаслідок того , що аₙ = 1/ [ (3n-1)*(3n+2) ] = 1/3 * [1/(3n - 1 ) - 1/(3n + 2 )] ,
маємо : А = 1/3 *( 1/2 - 1/5 ) + 1/3 *( 1/5 - 1/8 ) + 1/3 *( 1/8 - 1/11 ) + ... +
+ 1/3 * [1/(3n - 1 ) - 1/(3n + 2 )] = 1/3 *( 1/2 - 1/( 3n + 2 ) ) = 3n/[6( 3n + 2 ) ] =
= n/[ 2( 3n + 2 ) ] .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь: n/[ 2( 3n + 2 ) ] .
Пояснення:
Нехай А = 1/(2*5) + 1/( 5*8) + 1/( 8*11 ) +...+ 1/ [ (3n-1)*(3n+2) ] , тоді,
внаслідок того , що аₙ = 1/ [ (3n-1)*(3n+2) ] = 1/3 * [1/(3n - 1 ) - 1/(3n + 2 )] ,
маємо : А = 1/3 *( 1/2 - 1/5 ) + 1/3 *( 1/5 - 1/8 ) + 1/3 *( 1/8 - 1/11 ) + ... +
+ 1/3 * [1/(3n - 1 ) - 1/(3n + 2 )] = 1/3 *( 1/2 - 1/( 3n + 2 ) ) = 3n/[6( 3n + 2 ) ] =
= n/[ 2( 3n + 2 ) ] .